Crafting Communities: Empowering Bezuidenhout Valley Through Construction Workshops: A Blueprint for Self-Sufficiency and Collaboration - Maxwell , Ryan (University of the Witwatersrand, Johannesburg, 2024)
South Africa faces significant challenges in areas such as housing, job security, and skill development and addressing these issues requires a holistic approach. Providing training in construction skills enables the people to build necessary infrastructure like housing, training centers, and social spaces. In addition to this, many communities have spaces that are underutilized or neglected due to various factors such as limited accessibility, safety concerns (demolished buildings, dumping sites, etc), or distance from central areas. Despite these drawbacks, people often find ways to occupy these spaces. Why do they choose to use these areas? The utilization of such spaces typically stems from a lack of alternative options for housing, commerce, or social activities. In the blue-collar northeastern areas of Johannesburg such as Bezuidenhout valley, residents face a multitude of challenges that undermine the quality of life and urban fabric. The Jukskei River, a vital waterway, suffers from pollution, affecting both the environment and public health. Additionally, the community suffers from high unemployment rates and a significant skills shortage. Housing is insufficient, and many existing structures are in a state of disrepair, further compounding social and economic issues. The theories that have influenced my thinking and response are resilience, densification, sustainability, Renewable materials, the Garden city, and hands on teaching. These theories help to understand and view urban areas as dynamic systems and productive environments. “Productivity” in this context includes economic, social, cultural, and environmental dimensions. By addressing these factors, we create a foundation for identifying, planning, and designing appropriate interventions through research and design. The central research theme focuses on the connection between architecture and resilient urban spaces Architecture offers a unique opportunity to address these interconnected issues by empowering the community through construction skills training. By establishing a construction and learning center, residents can gain practical skills while contributing to the development of essential infrastructure, such as housing, training centers, craft spaces for entrepreneurs and social spaces. This approach not only addresses immediate needs but also fosters long-term socio-economic growth
A research report submitted in fulfillment of the requirements for the Master of Architecture, In the Faculty of Engineering and the Built Environment , School of Architecture and Planning, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Phytoremediation; Bamboo self build structures; Community Engagement; SDG-8: Decent work and economic growth